2005
DOI: 10.1111/j.1466-822x.2005.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological behaviour of herbaceous forest species along a pH gradient: a comparison between oceanic and semicontinental regions in northern France

Abstract: Aim On the basis of 2402 phytoecological relevés, with complete species lists, and real pH measurements resulting from chemical analyses of the top layer of forest soils, this paper compares quantitatively the ecological response of 46 herbaceous forest species along a pH gradient in two regions of northern France. LocationThe two regions investigated are oceanic north-western France (NW) and semicontinental north-eastern France (NE). MethodsFor each of the 46 species with more than 50 occurrences in both NW a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…6 Species response curves, fitted by Huisman-Olff-Fresco (HOF; Oksanen and Minchin 2002a, b) modelling for 19 species (frequency >5%) on the basis of 2,691 1-m 2 plots, displaying each species' probability of occurrence with respect to the elevational gradient in relation to MHT (cm; zero line dotted). For each species, the estimated lower and upper limit are highlighted (solid lines) to mark species' amplitude (Gégout and Pierrat 1998;Coudun and Gégout 2005). For a summary of model types and parameters of the response curves see Electronic Appendix 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Species response curves, fitted by Huisman-Olff-Fresco (HOF; Oksanen and Minchin 2002a, b) modelling for 19 species (frequency >5%) on the basis of 2,691 1-m 2 plots, displaying each species' probability of occurrence with respect to the elevational gradient in relation to MHT (cm; zero line dotted). For each species, the estimated lower and upper limit are highlighted (solid lines) to mark species' amplitude (Gégout and Pierrat 1998;Coudun and Gégout 2005). For a summary of model types and parameters of the response curves see Electronic Appendix 2.…”
Section: Discussionmentioning
confidence: 99%
“…Under field conditions 'physiological niches' of species are usually constrained by competition (see Ellenberg et al 1992). There are various parameters for describing 'ecological niches' (Hutchinson 1957) including minima-maximaranges (Bockelmann et al 2002), medians (Sánchez et al 1996;Silvestri et al 2005), tolerances (ter Braak and Looman 1986;Schröder et al 2005), or amplitudes (Coudun and Gégout 2005;Peppler-Lisbach 2008). Species response curves are another useful tool (ter Braak and Looman 1986;Gégout and Pierrat 1998;Pakeman et al 2008) to link species' presence/absence or abundance data to gradients.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this context, the continuum model (Austin 1999) is being taken into consideration through the definition of habitat gradients and creates an explicit link between species' distribution patterns and ecological processes (Fischer and Lindenmayer 2006). Most of the studies about response curves along an ecological gradient have been conducted on plant species (Austin 2002;Oksanen and Minchin 2002;Rydgren et al 2003;Coudun and Gegout 2005;Yee 2006) and relatively little research has focused on response curves for animals describing ecological processes at the landscape scale (Suárez-Seoane et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient gradient expressed by the first axis was practically identical in both regional samples despite the change in floristic composition. Moreover, Coudun and Gégout [18] recently showed that the pH behaviour of plant species is close in the north-eastern and north-western part of France: the correlation between regional pH indicator values is 0.78 and 75% of the species have regional pH indicator values differences lower than 0.5.…”
Section: Understory Vegetation As a Relevant Indicator Of Site Producmentioning
confidence: 99%